"Dancing Eye Syndrome" Secondary to Opsoclonus-Myoclonus Syndrome in Small-Cell Lung Cancer. (23rd March 2014) - Laroumagne, S.; Elharrar, Xavier; Coiffard, B.; Plojoux, J.; Dutau, H.; Breen, D.; Astoul, P.
Abstract : Among paraneoplastic neurologic disorders (PND), opsoclonus-myoclonus syndrome, so-called "dancing eye syndrome, " is a rare disorder combining multivectorial eye movements, involuntary multifocal myoclonus, and cerebellar ataxia. Although several paraneoplastic antibodies against postsynaptic or cell-surface antigens have been reported, usually most patients are serum antibody negative. We report a 65-year-old patient with opsoclonus-myoclonus syndrome revealing a small-cell lung carcinoma. If serologic antineuronal anti-body screening was negative, autoantibodies against glutamic acid decarboxylase (anti-GAD) were positive. Despite the specific anticancer treatment and high dose corticosteroids, the patient developed a severe and progressive encephalopathy and died 10 days later.